Nintendo WII contribution to sports biomechanics: a pilot study of push-off kinematics in breaststroke swim turn - Shahbazi, M.; Schogler, B.; Sanders, R.; Koenig, F. (ISBS - Conference Proceedings Archive (Konstanz), 2008)
WII, as accelerometer was used to study push-off phase in breaststroke swim turn. The accelerometer could not be used directly into the water; therefore necessary modifications had to be done in order to use it in water. The results have been compared with the results of Qualisys Motion Analyzer system and theoretical modelling. A comparison of three results showed that the Nintendo WII acceleration power was 0.978 (r=0.989) very near the theoretical one (r=1), while the digitized filming showed a poorer power of 0.443 (r=0.67).The main problem with WII system was the noise that in our pilot study was not properly coped. The results obtained were reasonable and opened a new window for the use of Nintendo WII system in future research.